A RARE TUMOUR OF CAUDA EQUINA: A CASE REPORT. (February 2015) - Shein, Tint T.; Sheehy, John; Morey, Adrienne
Abstract : Aims: Description of a rare case of cauda equina: Capillary haemangioma. Method: Review of histopathology, imaging and literature. Result: A 44-year-old lady presented with recent-onset left-sided low back pain radiating to anterior thigh. She had a back injury nine years prior; magnetic resonance imaging (MRI) then showed a low termination of spinal cord at L2/3 level and a small intraspinal lipoma. The recent MRI showed an intraspinal enhancing mass at L2/3 with nerve root displacement to the right. In light of significant progression in size over the nine-year period, the intradural red fleshy tumour adherent to multiple nerve roots of the cauda equina was subsequently removed. A 22 × 10 × 5 mm dark-brown lobulated tumour was received. Histologically, there was a circumscribed pseudoencapsulated CH arising within a substantial nerve trunk. Variably sized vascular spaces were arranged in lobular pattern and lined by bland endothelial cells (ERG-positive and S100-negative). Discussion: CHs are commonly seen as cutaneous and mucosal lesions. CHs of the cauda equina are extremely rare and clinically simulate schwannoma, ependymoma, or neurofibroma. To our knowledge, only 19 cases have been previously described since publication of the earliest report in 1987. It should be considered as a differential diagnosis in middle-aged patients with enhancing lesions of the cauda equina.